(untitled) (Research, Society and Development, 2021)
Modified atmosphere packaging (MAP) was evaluated for respiration rate, color, total phenolic content (TPC), antioxidant activity DPPH, flavonoids and pigments of fresh-cut Tropic Beauty peach. Modified atmospheres (21% O2 [Control], 5% CO2 [MAP1], 8% CO2 [MAP2] and 0% O2 [MAP3]) were evaluated for storing fresh-cut peaches for up to 10 days in temperatures of 5ºC. MAP significantly (p<0.05) affected the proprieties investigated as compared to control. Peaches with MAP3 have higher respiration(p<0.05) respiration rate than the peaches with the other treatments. Fresh-cut peaches in MAP2 showed more stable (p<0.05) carotenoid and anthocyanin contents, better attributes in the bioactive compounds. MAP1 and MAP2 exhibited better antioxidant proprieties at low storage temperature (5ºC) for up to 10 days storage and similar result was verified by principal component analysis used where modified atmosphere was observed as major factor.